Magnetic assistance in laser powder directed energy deposition - Smith, Peter H. (2022)
Directed energy deposition is an additive manufacturing process characterised by the concurrent delivery of material and energy in order to consolidate material into a desirable component geometry. The process is useful as a coating technique to improve wear and chemical resistance in the nuclear industry; it is used to repair worn dies in the automotive industry, and is also used for the near-net shape manufacturing of large components in the aerospace industry. The material deposition efficiency, and particularly the powder catchment efficiency (the ratio of consolidated powder to total powder input) is critical to both the cost-effectiveness of the process, and its overall accuracy. Loss of this powder into the surrounding environment can also be hazardous. To tackle these issues, this work uses magnetic fields to improve the level of control over powder flow and improve catchment efficiency in laser powder directed energy deposition. Magnetic control of powder flow has potential to be a practically implementable technique to precisely change the quantity and direction of powder entering the melt pool in laser directed energy deposition (LDED). This work demonstrates the use of magnetic assistance, and examines how different directed energy deposition parameters, such as the powder feed rate, laser power and scanning speed affect the efficacy of magnetic assistance. In addition, the dependence of process performance on magnetic parameters including the size, strength and placement of magnetic fields, is also determined and discussed. Hardness, surface roughness, composition and porosity are also examined. Magnetic fields are shown to provide a 50.8 % improvement in catchment efficiency, increasing the width of tracks by at least 25%, whilst also reducing the dilution in depositions made using ferromagnetic powders. An improved powder catchment efficiency has potential to drastically reduce the cost of manufacturing, especially considering the large size of components which can be manufactured using this technology and the high cost of powder (which can easily be above £400 per kg). Furthermore, magnetic field strength is shown to have a positive relationship with track size, suggesting that altering magnetic field strength may allow magnetic assistance to be used in a discrete fashion. The technique is also proposed and examined for its potential as a new control method, by varying the placement and dynamically changing magnetic fields during deposition. Similar geometric outcomes were achievable over specific portions of the deposition, when switching magnetic fields dynamically, suggesting that magnetic assistance is an effective dynamic control technique. It is currently difficult to alter track dimensions during operation, therefore this technique has the potential to give the technology significant greater potential. The fundamental mechanism of magnetic assistance is also examined and discussed in detail, by comparing the effects of magnetic powder pre-loading over a large magnetic field in contrast to feeding powder over a smaller coaxial magnetic field. This work acts as the first in this field, thus considers the potential future of magnetic assistance in three dimensional additive manufacturing, though it is limited to two dimensional tracks in this work, due to the magnetic field being located beneath the substrate. To develop the technique in a greater range of materials demonstration of enhanced deposition through magnetic assistance of more complex alloy systems, in particular those that are not entirely ferromagnetic is also performed, using composite bespoke powder systems. Further to improving the materials efficiency; in future, the technique has potential for use as an adaptive control technique, to vary the powder catchment efficiency in process, dynamically altering the dilution into the substrate and the track geometry as is necessary, though currently it is mainly restricted to ferromagnetic alloys, or those with a significant component.